The Influence of Financial Literacy and Digital Financial Competency on Advanced consumption of Student Behavior: The Mediating Role of Self-Control in Wuhan University of Technology in China - Houbianbian; Fridayana Yudiaatmaja; Putu Indah Rahmawati (LP2M IAIN Palopo, 2026)
The rapid expansion of the digital economy and fintech infrastructure has fundamentally restructured the consumption patterns of university students, leading to a rise in credit-enabled advanced consumption. This research aims to investigate the determinants of advanced consumption behavior by integrating cognitive financial assets and psychological self-regulation mechanisms. Specifically, the study examines the influence of financial literacy and digital financial competency on advanced consumption, with self-control serving as a potential mediating variable. A quantitative research design was employed, utilizing Structural Equation Modeling (SEM) to analyze data collected from university students. The empirical results demonstrate that both financial literacy and digital financial competency exert a significant negative influence on advanced consumption behavior. Notably, digital financial competency emerged as a more potent predictor, suggesting that in a platform-mediated economy, the ability to navigate digital choice architecture is a critical deterrent to excessive spending. Furthermore, the analysis reveals that self- control significantly mediates the relationship between these financial capabilities and consumption outcomes. Approximately 39% of the impact of financial knowledge on reducing debt-funded consumption is transmitted through the strengthening of internal regulatory mechanisms.These findings underscore the necessity of a holistic approach to financial education. Beyond traditional numeracy, academic and policy interventions should prioritize critical digital literacy and the development of psychological resilience. Strengthening the